2013
DOI: 10.1111/hiv.12117
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and risk factors for pulmonary abnormalities in HIV‐infected patients treated with antiretroviral therapy

Abstract: BackgroundPulmonary abnormalities are often present in patients infected with the human immunodeficiency virus (HIV). ObjectivesThe aim of the study was to determine the prevalence and characteristics of, and risk factors for, pulmonary abnormalities in HIV-positive patients. MethodsA total of 275 HIV-positive patients [mean (± standard deviation) age 48.5 ± 6.6 years] were included in the study, of whom 95.6% had been receiving highly active antiretroviral therapy (HAART) for a mean (± standard deviation) dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 37 publications
4
69
0
1
Order By: Relevance
“…Sampériz et al [3] observed the presence of airflow limitation, decreased air diffusion capacity, finding smoking and previous TB infection as the main risk factors, as found in our case.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Sampériz et al [3] observed the presence of airflow limitation, decreased air diffusion capacity, finding smoking and previous TB infection as the main risk factors, as found in our case.…”
Section: Resultssupporting
confidence: 81%
“…In conclusion, an association was suggested between respiratory alterations with advanced age, smoking habit and high viral loads. In turn, it was shown that ARV treatment is an independent predictor of increased airway obstruction [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Our findings are consistent with Samperiz and colleagues who reported no relation between quantitative assessment of emphysema on CT scan and either HIV viral load or CD4 count. 52 However, they reported that the Center for Disease Control HIV category C was a risk factor for quantitative emphysema and a modest emphysema prevalence (10.5%) using a low emphysema cutoff (greater than 1% of voxels with a value less than -950HU). Three recent studies of HIV-infected cohorts 46,48,52 observed that greater than 30% of the subjects had some evidence of emphysema by visual CT image assessment, which is somewhat higher than our findings of 25.1% by quantitative analysis.…”
Section: Discussionmentioning
confidence: 98%
“…46,48-52 Furthermore, to our knowledge only two studies performed quantitative CT analyses. 27,52 A quantitative approach may be more sensitive to detect correlations between lung abnormalities on radiographic images and biological/physiological measures as well as to detect lung abnormalities at an earlier stage compared to subjective visual image review.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the availability of highly active antiretroviral therapy and the widespread use of PJP prophylaxis [20], the latter still is one of the commonest opportunistic infections in HIV+ patients [21,22]. Additionally, the high mortality of patients with PJP requiring mechanical ventilation remains unchanged (50-60%) [23].…”
Section: Discussionmentioning
confidence: 99%